Особенности фенологии некоторых видов тропических и субтропических растений в условиях защищенного грунта - Горницкая, И.П.; Ткачук, Л.П. (Промышленная ботаника, 2003)
The data on the strategies of growth and flowering of species, originating from two macroterritories of dry land – Mediterranean and Western Pacific geosynclinal belts, under the conditions of the Donetsk Botanical Gardens, Nat. Acad. Sci. of Ukraine conservatories, are presented. The higher absolute values of deviation in terms of flowering from the average long-term ones of the speciess originating from the Mediterranean geosynclinal belt may be accounnted for by their higher tolerance and better capacity of adaptation to the changeable conditions of the ground used for introduction. The percent of the species with a complete development cycle and full-grained seed production is also higher among the representatives of the Mediterranean geosynclinal belt, that allows to expect a greater success of introduction of these species.